Research Hotspots and Trend Exploration on the Clinical Translational Outcome of Simulation-Based Medical Education: A 10-Year Scientific Bibliometric Analysis From 2011 to 2021 - Yao, Shun; Tang, Yabin; Yi, Chenyue; Xiao, Yao (Frontiers in Medicine, 2022)
Background: In recent decades, an increasing number of studies have focused on the practical effect of simulation-based medical education and have shown its positive effects on clinical skill translation. However, few scientific bibliometric studies have analysed the quantities of publications. This study aimed to systematically investigate research hotspots and development trends in this field through bibliometric analysis. Method: Relevant publications on the clinical translational outcomes of simulation-based medical education from 2006 to 2020 were identified and retrieved from the Web of Science Core Collection. Software including VOSviewer (5.7.R5) and CiteSpace (1.6.16) and a platform (bibliometric.com) were used to conduct this scientometric study. Results: A total of 962 publications were analysed in this study. An increasing number of publications were observed. The United States accounted for the largest number of publications and citations, followed by Canada; the University of Toronto and Northwestern University were the leading institutions. Academic Medicine led the top 10 most productive cocited journals. William C McGaghie and Diane B Wayne were the most influential authors in this area. The translational effect of specific technical skills that included paediatric skills, endoscopy, the central venous catheter, crisis management, and laparoscopic surgery and nontechnical skills such as teamwork and communication are current research hotspots. Translational outcomes from deliberate practice to bedside setting skills obtained from meta-analysis and random controlled trials are further needed. Conclusion: This study summarized the current research hotspots and development trends of the clinical translational outcomes of simulation-based medical education, which may help scholars promote research seeking to determine the exact effects to provide evidence for more common and widespread usage of simulation-based medical education in future preclinical medical education